Mindfulness-Based Asmaul Husna and changes in general adaptive function response among schizophrenia: A Quasi-experimental study - Inggriane Puspita Dewi; Hartiah Haroen; Hanna Rizmadewi Agustina; Tuti Pahria; Shella Febrita Putri Utomo; Popy Siti Aisyah; Icih Susanti (Jurnal Keperawatan Padjadjaran, 2024)
Background. Poor functional capacity is one of the factors that increase the risk of recurrence of positive and negative symptoms in schizophrenia. Mindfulness is a treatment potentially help patients become fully accepting of their conditions and conscious of it, allowing them to regulate unpleasant emotions and increase awareness of positive emotions. Methods. This study aimed to investigate effect of mindfulness-based Asmaul Husna on the overall adaptive functioning of individuals with schizophrenia. This quasi-experiment times series study involved 36 participants selected with simple random sampling. The inclusion criteria of participants were adult Muslim with schizophrenia who had a PANSS-EC score <10, mild symptoms, risk of violent behavior. Participants with severe symptoms and complications from other diseases were excluded. Mindfulness-based Asmaul Husna consisted of Musyahadah-witnessing, tassawur-imagination, tafakkur-contemplation, tadabbur-reflection, and muhasabah-self-introspection was given to each participant over five days. A modified-Global Assessment Functioning (m-GAF) scale used to measure participants' general adaptive functional responses before and after intervention including follow-up at the first and second month after the intervention. Results. There was a significant increase of the m-GAF score (p < 0.001) and a chi-square value of 177.2 after the implementation of mindfulness-based Asmaul Husna intervention. The highest mean score difference was observed at the first and second follow-ups, conducted one and two months after the interventions. The effect size calculated using Kendall’s Wa indicates a significant effect (0.821). Conclusion. The study suggests there is a positive effect of the mindfulness-based Asmaul Husna intervention on adaptive functioning of people with schizophrenia.